The Jet Makers The Aerospace Industry from 1945 to 1972 - Bright, Charles D. (University Press of Kansas, 1978)
This volume presents the history of the American jet aircraft manufacturing industry from World War II to 1972, documenting the evolution of its technology and covering the intricacies of its management, economics, and relations with the government. A valuable contribution to general aviation history, it also provides a unique opportunity to study the dynamic of a major U.S. industry.Charles D. Bright traces the momentous revolution of the aerospace era from birth to maturity, using as a base the jet aircraft industry. He investigates all significant aspects: the comingofage of aviation during World War II, including global transportation and aerodynamics; the development of jets and missiles from the Truman era to the Vietnam War; the controlling influence of national military strategy; the U.S. Air Force and other government markets; the mechanics of government procurement-bidding, pricing, buying; difficulties in the commercial airliner business; the ordering of technology and the prevailing "design or die" philosophy; and different systems of production through the years.Special attention is given to major problems such as the industry's need for diversification and the skyrocketing costs that threaten to make aerospace products uneconomical. The conventional economic concerns of entry into and exit from the industry are treated in depth. Bright focuses on the overall economic pattern, from the first demand for aerospace machines for military, space, and commercial uses to the failures of recent times as the industry entered recession and peacetime equilibrium. He tells of the desperate competition among giants of the industry, those companies on the frontiers of technology that manufactured fixedwing aircraft of their own design. This is the group that bore the brunt of adaptation to the jet age: Boeing, CurtissWright, Douglas, Fairchild, General Dynamics, Grumman, Lockheed, martin, McDonnell, North American Northrop, and Republic.Central to the story are the reasons for America's leadership in the jet age: enterprising business managers, scientists, and engineers; the pressure of economics; and manifold competition brought on by economics; and manifold competition brought on by the cold war. Bright points to an industry that has responded to incredible demands and that has shown the strength to weather storms.This volume is illustrated with fiftyfive photographs depicting the growth in aircraft technology from 1945 to 1972. As a unique blend of aeronautic, economic, business, and military history, it will fascinate not only those connected with aviation and the aerospace industry, but also those interested in the history of technology, business management, and governmentmilitarybusiness relations.The Jet Makers received Honorable Mention in the 1977 History Manuscript award competition of the American Institute of Aeronautics and Astronautics.